Digital technology and the allocation of ownership in the music Industry - Maija Halonen-Akatwijuka; Tobias Regner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
We apply the property rights theory of Grossman-Hart-Moore in the music industry and study the optimal allocation of copyright between the artists who create music and the labels who promote and distribute it. Digital technology opens up a role for new intermediaries. We find that entry of online platforms occurs only if they are sufficiently more productive in distribution than the incumbent label. Furthermore, entry leads to a change in bargaining positions and it can become optimal for the copyright to be shifted from the label to the artist.
Keywords: D23; L22; L23; L82; L86; 330; property rights theory; copyright; internet music industry; Musikwirtschaft; Internet; Digitale Güter; Urheberrecht; Eigentumsrechtstheorie; Arbeitsteilung; Theorie